Cooperative effects of hydrogen sulfide and nitric oxide on delaying softening and decay of strawberry - Chang, Zhang; Jingying, Shi; Liqin, Zhu; Changle, Li; Qingguo, Wang (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: Hydrogen sulfide (H2S) and nitric oxide (NO) as two signal molecules play prominent roles in plant response to biotic stress. The combination effects of these two molecules on ripening and decay of postharvest strawberry were investigated. Strawberries were first dipped in distilled water, 0.8 mmol/L NaHS solution, 5 µmmol/L sodium nitroprusside (SNP) solution, and combinative solutions of 0.8 mmol/L NaHS and 5 µmmol/L SNP for 10 min, respectively, and then stored at 20°C. Results showed that the effects of the co-treatment of 0.8 mmol/L NaHS solution and 5 µmmol/L SNP solution were superior to that of other treatments. The former could suppress the percentage of fruit decay, inhibit respiration rate, maintain the original crust color, and slow down the decrease of firmness and the change of relative conductivity, which preserved the fruit quality. Further investigation showed that co-treatment of hydrogen sulfide and nitric oxide maintained higher activities of chitinase (CHI) and beta-1,3-glucanase (GNS), and lowered activities of pectin methylesterase (PME), polygalacturonase (PG) and endo-β-1,4-glucanase (EGase). The study indicated that the synergistic function of H2S and NO could effectively prolong the shelf life and reduce the decay rate of harvested strawberry. Keywords: hydrogen sulfide, nitric oxide, strawberry, enzyme activities, shelf life DOI: 10.3965/j.ijabe.20140706.014 Citation: Zhang C, Shi J Y, Zhu L P, Li C L, Wang Q G. Cooperative effects of hydrogen sulfide and nitric oxide on delaying softening and decay of strawberry. Int J Agric & Biol Eng, 2014; 7(6): 114－122